2014
DOI: 10.3141/2443-08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Traffic Load Input Level on Mechanistic–Empirical Pavement Design

Abstract: This study investigated the effect of the input level of axle load spectra on performance predictions obtained with the Mechanistic–Empirical Pavement Design Guide (MEPDG). Traffic monitoring data collected from 50 weigh-in-motion (WIM) stations distributed across the state of Ohio were analyzed to obtain site-specific and regional axle load spectra. The site-specific axle load spectra were calculated for each axle group (single, tandem, tridem, and quad) and truck class (Classes 4 through 13). The regional ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Es siempre delicado tratar la representatividad estadística de los resultados obtenidos en muestras tan pequeñas, y más A este respecto puede destacarse el trabajo de Abbas et al (18), que evaluó la diferencia en la estimación de la vida de servicio de varios diseños básicos de pavimentos flexibles de la MEPDG según se utilizaban diferentes espectros de cargas: los específicos para cada lugar obtenidos mediante pesaje dinámico o algunos dados por defecto en la norma. Tras el análisis se observó que los espectros dados por defecto en la MEPDG infraestimaban claramente la vida de servicio del pavimento (del orden del 50 %) y, por tanto, si se utilizaban para el dimensionamiento resultaban unos espesores de capas muy conservadores.…”
Section: Representatividad Estadística De Los Resultadosunclassified
“…Es siempre delicado tratar la representatividad estadística de los resultados obtenidos en muestras tan pequeñas, y más A este respecto puede destacarse el trabajo de Abbas et al (18), que evaluó la diferencia en la estimación de la vida de servicio de varios diseños básicos de pavimentos flexibles de la MEPDG según se utilizaban diferentes espectros de cargas: los específicos para cada lugar obtenidos mediante pesaje dinámico o algunos dados por defecto en la norma. Tras el análisis se observó que los espectros dados por defecto en la MEPDG infraestimaban claramente la vida de servicio del pavimento (del orden del 50 %) y, por tanto, si se utilizaban para el dimensionamiento resultaban unos espesores de capas muy conservadores.…”
Section: Representatividad Estadística De Los Resultadosunclassified
“…Certainly, they did not take some factors such as the distribution of traffic flow in different road sections, lanes, time periods (day and nights), and vehicle speed into consideration at the same time. Nevertheless, with the development of radio frequency identification technology, dynamic weighing technology, and high-definition image recognition technology, network tolling systems, weightcalculating charge systems, and high-definition video surveillance systems have been widely used in highway operation management faced with increasing traffic volume (Abbas et al, 2014;Ren et al, 2019;Feng et al, 2020). Massive traffic data are being collected on every expressway every day.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…Although previous studies have employed similar clustering techniques, it is important to note that different traffic characteristics were used for clustering analysis. Papagiannakis et al used the tandem axle spectra as the only representative axle type, and thus the clustering of single, tridem, and quad axle load spectra followed the identified one for tandem axles ( 4 , 17 ). Sayyady et al and Lu and Harvey conducted cluster analysis on tandem axles, and modified the identified clusters for single, tridem, and quad axles considering the geographic/functional assignment of roads using engineering judgment ( 3 , 6 ).…”
mentioning
confidence: 99%